Eradication rate and histological changes after Helicobacter pylori eradication treatment in gastric cancer patients following subtotal gastrectomy - Hwang, Jae Jin (World J Gastroenterol, 2015)
AIM: To investigate the eradication rate and histological changes after Helicobacter pylori (H. pylori) eradication treatment following subtotal gastrectomy for gastric cancer. METHODS: A total of 610 patients with H. pylori infection who had undergone surgery for either early or advanced gastric adenocarcinoma between May 2004 and December 2010 were retrospectively studied. A total of 584 patients with proven H. pylori infection after surgery for gastric cancer were enrolled in this study. Patients received a seven day standard triple regimen as first-line therapy and a 10 d bismuth-containing quadruple regimen as second-line therapy in cases of eradication failure. The patients underwent an esophagogastroduodenoscopy (EGD) between six and 12 mo after surgery, followed by annual EGDs. A further EGD was conducted 12 mo after confirming the result of the eradication and the histological changes. A gastric biopsy specimen for histological examination and Campylobacter-like organism testing was obtained from the lesser and greater curvature of the corpus of the remnant stomach. Histological changes in the gastric mucosa were assessed using the updated Sydney system before eradication therapy and at follow-up after 12 mo. RESULTS: Eradication rates with the first-line and second-line therapies were 78.4% (458/584) and 90% (36/40), respectively, by intention-to-treat analysis and 85.3% (458/530) and 92.3% (36/39), respectively, by per-protocol analysis. The univariate and multivariate analyses revealed that Billroth II surgery was an independent factor predictive of eradication success in the eradication success group (OR = 1.53, 95%CI: 1.41-1.65, P = 0.021). The atrophy and intestinal metaplasia (IM) scores 12 mo after eradication were significantly lower in the eradication success group than in the eradication failure group (0.25 ± 0.04 vs 0.47 ± 0.12, P = 0.023; 0.27 ± 0.04 vs 0.51 ± 0.12, P = 0.015, respectively). The atrophy and IM scores 12 mo after successful eradication were significantly lower in the Billroth II group than in the Billroth I group (0.13 ± 0.09 vs 0.31 ± 0.12, P = 0.029; 0.32 ± 0.24 vs 0.37 ± 0.13, P = 0.034, respectively). CONCLUSION: Patients with H. pylori following subtotal gastrectomy had a similar eradication rate to patients with an intact stomach. H. pylori eradication is recommended after subtotal gastrectomy.